2021
DOI: 10.3389/fpls.2021.695908
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor Application in Strawberry Results in Long-Term Increase of Plant Resilience Without Yield Loss

Abstract: For a first step integrating elicitor applications into the current IPM strategy increasing plant resilience against pests, we investigated repeated elicitor treatments in a strawberry everbearer nursery and cropping cycle under glass. During nursery methyl-jasmonate (MeJA), testing induction of defenses with plant bioassays was applied every 3 weeks. Thrips damage and reproduction by spider mites, whitefly and aphids were strongly reduced upon elicitor treatment. Subsequently, we applied MeJA every 3 weeks or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
5
0
4
Order By: Relevance
“…For example, Steinite and Levinsh (2002 , 2003) showed that induced resistance in strawberry, indicated by increased polyphenol oxidase, which is an important JA-inducible marker, negatively affected reproduction of T. urticae . Mouden et al (2021) reported that induction of the JA pathway enhanced strawberry plant defense against T. urticae via increased production of phenolic acids, flavonoid compounds and anthocyanins. Similarly, Luczynski et al (1990) observed that the development of T. urticae correlated negatively with foliar concentrations of phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Steinite and Levinsh (2002 , 2003) showed that induced resistance in strawberry, indicated by increased polyphenol oxidase, which is an important JA-inducible marker, negatively affected reproduction of T. urticae . Mouden et al (2021) reported that induction of the JA pathway enhanced strawberry plant defense against T. urticae via increased production of phenolic acids, flavonoid compounds and anthocyanins. Similarly, Luczynski et al (1990) observed that the development of T. urticae correlated negatively with foliar concentrations of phenolics.…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonic acid and its biologically active derivatives (collectively known as jasmonates or JAs) are essential molecular tools in shaping the defensive response to a broad spectrum of pathogens and insects (Hazman et al, 2019;Mouden et al, 2021). (Qi et al, 2018) reported that UV-B exposure for five days significantly elevated jasmonic acid hormone (JA) and synthesizing genes expression as AtOPR3 in Arabidopsis, and NtAOC, OsLOX, and ZmJAR1 in tobacco, rice, and maize, respectively.…”
Section: A B Discussionmentioning
confidence: 99%
“…Deze chemische elicitor zorgt ervoor dat planten sneller de jasmonzuurverdedigingsroute aanschakelen waardoor er sneller en meer secundaire metabolieten worden aangemaakt die de groei van insecten remmen. Ook in aardbei bleek deze elicitor langdurig de ontwikkeling van bladluis te remmen (Mouden et al 2021). Een recente Chinese studie liet zien dat de elicitor salicylzuur in graan de verdediging tegen graanluis kan verhogen, wat resulteerde in een significante lagere groeisnelheid (Feng et al 2021).…”
Section: Geïnduceerde Plantweerbaarheidunclassified
“…Deze chemische elicitors bieden dus wellicht mogelijkheden om de plantweerbaarheid tegen bladluis te verhogen. In de recente studie van de WUR bleek toepassing van MeJa in aardbei geen effecten te hebben op de opbrengst (Mouden et al 2021).…”
Section: Geïnduceerde Plantweerbaarheidunclassified